MAMA'S Neighborhood–Maternity Assessment Management Access & Service Synergy Through the Neighborhood for Health [16L]. (May 2017) - Saleeby, Erin; Scibetta, Emily; Moini, Moraya; Trang, Cassandra; Young, Carmen Canto; Greenwell, Lisa
Abstract : INTRODUCTION: MAMA's Neighborhood (MAMAs), funded by the Strong Start for Mothers and Newborns Initiative, aims to evaluate models of prenatal care to reduce preterm (PTB) and low birth weight (LBW). Using a medical home model in high prevalence areas of Los Angeles, MAMAs sought to better assess potential social determinants of PTB and LBW and organize care to address these risks via: 1. Collaborative care teams, 2. Risk stratified case management, 3. Population health management, and 4. Community engagement and care delivery with social-service agencies. METHODS: Data were collected December 2013–August 2016. MAMAs implemented a novel initial assessment with evidence-based screening tools for psychosocial risk factors, risk stratification, case management and population health tracking by collaborative care teams at 6 sites. Neighborhood services were linked for individualized care planning. RESULTS: A total of 3, 214 women enrolled. This cohort exhibited disproportionately high rates of food insecurity (15%), depression (23%), anxiety (31%) and intimate partner violence (32%) when compared to the general obstetric population. All women received risk stratified case management, allocating services weekly to 4%, monthly to 23%, and trimesterly to 74% of the cohort. Neighborhood service referrals averaged 3.7 per participant for psychosocial needs. CONCLUSION: MAMAs Neighborhood successfully implemented evidence-based screening tools for psychosocial risk factors into prenatal care, risk stratify and manage population health. MAMAs also developed individualized care plans for pregnant women including services delivered by community-based agencies to meet social needs. This model, involving both health system and community partners, leverages a Neighborhood approach to optimize maternal-child health outcomes.